Effect of Acupuncture on Cognitive Function of Insomnia Patients Compared with Drugs: A Protocol for Meta-analysis and Systematic Review - Shan Qin; Jing Jiang; Wen-Zhong Wu; Xiao-Qiu Wang; Han-Qing Xi; Qin-Qin Fang; Bin Xu; Cheng-Yong Liu (Behavioural Neurology)
Insomnia, one of the most common sleep disorders, is thought to have an adverse effect on cognitive function. At the same time, people with cognitive dysfunction are more prone to insomnia. At present, pharmacotherapy is the main treatment for insomnia, but there are some shortcomings such as poor long-term efficacy and potential dependence. There is some evidence that acupuncture has some advantages in alleviating insomnia and improving cognitive function. This study is aimed at investigating the effects of acupuncture and drugs on cognitive function in patients with insomnia and evaluating the efficacy and safety of these two interventions, providing strong evidence for clinical decision-making. The study will retrieve eight major databases: China National Knowledge Infrastructure, Wanfang Database, VIP Database for Chinese Technical Periodicals, SinoMed, PubMed, Web of Science, Embase, and Cochrane Library. Dissertations, conference papers, and ongoing experiments will also be retrieved for supplement. Literature screening and data extraction will be completed by two authors independently (JJ and X-QW). If there were any disagreements, they would be discussed or referred to a third person for adjudication (W-ZW). Authors will use Cochrane risk of bias tool to assess the included studies. The Review Manager Statistical (RevMan) software is used to conduct the statistical process of meta-analysis, and funnel plot is used to evaluate reporting biases. The Grading of Recommendations Assessment Development and Evaluation (GRADE) Profiler can be used to be aware of the quality of evidence.